Positive electrode material, sodium ion battery and preparation method and application of sodium ion battery

By forming an artificial CEI film on the surface of the multi-metal oxide positive electrode material, the problem of poor structural stability and circulation performance of the sodium ion battery positive electrode material is solved, and the cycle stability and capacity retention rate of the battery are significantly improved.

CN119503907APending Publication Date: 2025-02-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411725263.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing sodium ion layered oxide positive electrode materials have problems such as complex phase transition, irreversibility, poor circulation performance and poor air stability, which affect the cycle life, storage and transportation of the battery.

Method used

A mixed solution of multi-metal oxide and organic solvent is used for drying, and an artificial solid electrolyte interface (CEI) film is formed on the surface of the positive electrode material through spontaneous oxidation reaction. The combination of high-entropy stability and carbonate organic solvents is used to improve the structural stability of the positive electrode material.

Benefits of technology

The cycle stability and circulation capacity retention rate of sodium ion batteries are significantly improved. After 600 weeks of circulation, the battery capacity retention rate can reach more than 89%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a positive electrode material, a sodium-ion battery, and a preparation method and application of the sodium-ion battery. The preparation method comprises the following steps: drying a mixed solution of a multi-element metal oxide and an organic solvent to obtain the catalyst, wherein metals in the multi-element metal oxide comprise a first metal and a second metal; the first metal is Na, and the second metal is selected from at least five of Ni, Cu, Mg, Fe, Co, Mn and Ti; the organic solvent comprises a carbonic ester organic solvent. The obtained positive electrode material has excellent structural stability, and can obviously improve the cycle performance of the sodium-ion battery when being used for the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode material, a sodium ion battery, and a preparation method and application thereof. Background Art

[0002] The existing sodium ion layered oxide cathode materials have the following main problems: 1) complex and irreversible phase transitions and poor cycle performance; 2) poor air stability. Among them, the stability problem is mainly that it is sensitive to H2O and CO2 and is prone to side reactions with the electrolyte, which in turn affects the cycle life, storage and transportation of the resulting battery.

[0003] At present, a stable solid solution can be formed by using multiple metal elements to occupy equivalent atomic sites. The synergistic effect and "cocktail effect" among the elements make the positive electrode material have a high degree of atomic disorder, a high density of edge dislocations and abundant oxygen vacancies, thereby improving the structural stability of the positive electrode material and the cycle performance of the resulting battery.

[0004] For example, patent application CN118198350A uses five transition metals to prepare a sodium ion layered oxide positive electrode material, which is intended to improve the structural stability of the material and the cycle stability of the resulting battery, but the cycle stability of the resulting battery is still poor.

[0005] Therefore, there is an urgent need for a positive electrode material with good stability and the ability to effectively improve the cycle performance of the resulting battery. Summary of the invention

[0006] In order to overcome the above defects in the prior art, the present invention provides a positive electrode material, a sodium ion battery and a preparation method and application thereof. The positive electrode material has excellent structural stability and can significantly improve the cycle performance of a sodium ion battery when used in the battery.

[0007] To achieve the above purpose, the present invention adopts the following technical solution.

[0008] The present invention provides a method for preparing a positive electrode material, which comprises the following steps: drying a mixed solution of a multinary metal oxide and an organic solvent to obtain the positive electrode material; wherein:

[0009] The metals in the multi-metal oxide include a first metal and a second metal; the first metal is Na, and the second metal is selected from at least five of Ni, Cu, Mg, Fe, Co, Mn and Ti;

[0010] The organic solvent includes a carbonate organic solvent.

[0011] In the present invention, during the drying process, the mixed solution forms a film on the surface of the multinary metal oxide through a spontaneous oxidation reaction at the particle-solvent interface. The obtained film is composed of reduced metal cations and metal-organic compounds, and has the performance of a solid electrolyte interface (CEI) film, which can also be called an artificial CEI film. Studies have found that by directly forming an artificial CEI film on the surface of the positive electrode material, especially when the film is formed on the surface of a multinary metal oxide with high entropy stability, the obtained positive electrode material can be used in a sodium ion battery, which can significantly improve the cycle stability of the sodium ion battery.

[0012] In the present invention, the carbonate organic solvent may refer to conventional carbonate organic solvents in the art, including carbonate organic solvents and fluorinated compounds thereof.

[0013] In some embodiments, the carbonate organic solvent is selected from one or more of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and fluorinated derivatives thereof.

[0014] In some embodiments, the carbonate organic solvent is PC, EC, DMC and EMC; the mass ratio of PC, EC, DMC and EMC is preferably (0.5-1):(0.5-1):(0.5-1):(0.5-1), and more preferably 1:1:0.5:0.5.

[0015] In some embodiments, the carbonate organic solvent is PC, fluoroethylene carbonate (FEC), EC, DMC and EMC; the mass ratio of PC, FEC, EC, DMC and EMC is preferably (0.5-1):(0.5-1):(0.5-1):(0.5-1):(0.5-1), and more preferably 1:0.5:0.5:0.5:0.5.

[0016] In some embodiments, the organic solvent further comprises an alkanone organic solvent; the alkanone organic solvent is preferably N-methylpyrrolidone (NMP).

[0017] In some embodiments, in the organic solvent, the mass ratio of the carbonate organic solvent to the alkane organic solvent is 0.1:1-5:1, preferably 3:1.

[0018] In some preferred embodiments, the organic solvent is PC, EC, DMC, EMC and NMP, and the mass ratio of PC, EC, DMC, EMC and NMP is preferably 1:1:0.5:0.5:1.

[0019] In some preferred embodiments, the organic solvent is PC, FEC, EC, DMC, EMC and NMP, and the mass ratio of PC, FEC, EC, DMC, EMC and NMP is preferably 1:0.5:0.5:0.5:0.5:1.

[0020] In some preferred embodiments, based on the mass of the mixed solution, the mass fraction of the multi-metal oxide is 20-30%, preferably 25%.

[0021] In some embodiments, the drying method is spray drying or oven drying; preferably, spray drying.

[0022] In some preferred embodiments, the spray drying has an inlet air temperature of 185°C and an outlet air temperature of 105°C.

[0023] In some embodiments, the preparation of the mixed solution comprises dispersing the multi-metal oxide in the organic solvent.

[0024] The dispersion is preferably performed by stirring and the time for the stirring and dispersing is preferably 12 hours.

[0025] In some embodiments, in the multinary metal oxide, the second metal is Ni, Cu, Mg, Fe, Co, Mn and Ti.

[0026] In some preferred embodiments, the chemical formula of the multinary metal oxide is Na (0.9-1) Ni (0.1-0.25) Cu (0.1-0.2) Mg (0.05-0.15) Fe (0.05-0.15) Co (0.05-0.1) Mn (0.1-0.25) Ti (0.1-0.25) O (1.9-2) .

[0027] In some specific embodiments, the chemical formula of the multi-metal oxide is NaNi 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O2.

[0028] In some embodiments, the multinary metal oxide further includes F. The anion part uses F to partially replace O. Compared with the M-O bond, the M-F bond has a higher strength. The partial replacement of O by F can improve the resistance to electrolyte corrosion and significantly enhance the structural and chemical stability of the material.

[0029] In some preferred embodiments, the chemical formula of the multinary metal oxide is Na (0.9-1) Ni (0.1-0.25) Cu (0.1-0.2) Mg (0.05-0.15) Fe (0.05-0.15) Co (0.05-0.1) Mn (0.1-0.25) Ti (0.1-0.25) O (1.9-2) F (0-0.1) .

[0030] In some specific embodiments, the chemical formula of the multi-metal oxide is Na 0.98 Ni 0.15 Cu 0.15 Mg 0. 1Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.98 F 0.02 .

[0031] In some specific embodiments, the chemical formula of the multi-metal oxide is Na 0.95 Ni 0.15 Cu 0.15 Mg 0. 1Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.95 F 0.05 .

[0032] In some specific embodiments, the chemical formula of the multi-metal oxide is Na 0.9 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.9 F 0.1 .

[0033] In some embodiments, the preparation method of the multi-metal oxide is a high temperature solid phase method.

[0034] In some preferred embodiments, the method for preparing the multinary metal oxide comprises the following steps:

[0035] S1, a mixed solution A of a second metal precursor and a solvent A, grinding, and sintering once;

[0036] S2, grinding, drying and secondary sintering of a mixed solution B of a product obtained by primary sintering, a first metal precursor and a solvent B.

[0037] In step S1, the second metal precursor is preferably selected from at least five of a Ni precursor, a Cu precursor, a Mg precursor, a Fe precursor, a Co precursor, a Mn precursor and a Ti precursor, for example, selected from at least five of NiO, CuO, MgO, Fe2O3, Co2O3, MnO2 and TiO2. The amount of the second metal precursor satisfies the stoichiometric ratio in the chemical formula of the multi-metal oxide.

[0038] In step S1, the solvent A is preferably anhydrous ethanol.

[0039] In step S1, when the multi-metal oxide further includes F, the mixed solution A further includes fluoride, such as sodium fluoride and / or ammonium fluoride.

[0040] In step S1, based on the total mass of the mixed solution A, the sum of the mass fractions of the second metal precursor and the fluoride is preferably 20%.

[0041] In step S1, the grinding is preferably performed in a sand mill.

[0042] In step S1, the grinding speed is preferably 2500 rpm.

[0043] In step S1, the grinding time is preferably 1 hour.

[0044] In step S1, the primary sintering is preferably performed in a tube furnace.

[0045] In step S1, the primary sintering temperature is preferably 450°C.

[0046] In step S1, the time of the first sintering is preferably 10 hours.

[0047] In step S1, the primary sintering is preferably performed by heating to 450°C at a heating rate of 3°C / min and then keeping the temperature for 10 hours.

[0048] In step S1, preferably, a rotary evaporation step is further included between the grinding and the primary sintering.

[0049] In step S2, the first metal precursor is preferably sodium carbonate.

[0050] In step S2, the solvent B is preferably anhydrous ethanol.

[0051] In step S2, the amount of the second metal precursor is preferably 1.05 times the theoretical amount of the second metal precursor (i.e., 5% excess), and the theoretical amount of the second metal precursor satisfies the stoichiometric ratio in the chemical formula of the multi-metal oxide, and those skilled in the art may know its specific meaning.

[0052] In step S2, the grinding is preferably performed in a sand mill.

[0053] In step S2, the grinding speed is preferably 2800 rpm.

[0054] In step S2, the grinding time is preferably 1.5 hours.

[0055] In step S2, the drying method is preferably spray drying or oven drying; more preferably spray drying.

[0056] The inlet air temperature of the spray drying is 185°C, and the outlet air temperature is 105°C.

[0057] In step S2, the secondary sintering is preferably performed in a tube furnace.

[0058] In step S2, the secondary sintering preferably includes the following steps: heating to 850°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, then reducing the temperature to 450°C at a rate of 3°C / min, and keeping the temperature for 3 hours.

[0059] In some embodiments, the method for preparing the multinary metal oxide comprises the following steps:

[0060] The mixed solution of the first metal precursor, the second metal precursor and the solvent is ground, dried and sintered to obtain the product.

[0061] The present invention also provides a positive electrode material, which is prepared by the positive electrode material preparation method as described above.

[0062] In some embodiments, the cathode material is as described above.

[0063] The present invention also provides a sodium ion battery, wherein the positive electrode of the sodium ion battery comprises the positive electrode material as described above.

[0064] The present invention also provides an application of the above-mentioned positive electrode material in the field of electrochemistry.

[0065] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0066] The reagents and raw materials used in the present invention are commercially available.

[0067] The positive and progressive effects of the present invention are:

[0068] The positive electrode material of the present invention forms an artificial CEI film on the surface of the multi-metal oxide, which not only has high entropy stability but also significantly improves the stability to air. When actually used in sodium ion batteries, the stability of the electrolyte interface is improved, thereby enhancing the cycle performance of the resulting battery. Specifically, after 600 cycles, the cycle capacity retention rate of the resulting battery can be as high as over 89%. DETAILED DESCRIPTION

[0069] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0070] Example 1

[0071] 1. Preparation of multi-metal oxides

[0072] According to the chemical formula Na 0.98 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.98 F 0.02 The corresponding multi-metal oxides were synthesized by a high temperature solid phase method.

[0073] First, according to the stoichiometric ratio in the general chemical formula, NiO, CuO, MgO, Fe2O3, Co2O3, MnO2, TiO2, and NH4F raw materials are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1 hour. After rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10 hours, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground at 2800rpm in a sand mill for 1.5 hours. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then decreased to 450℃ at a rate of 3℃ / min and kept warm for 3 hours, and then cooled to room temperature with the furnace to obtain a multi-metal oxide.

[0074] 2. Preparation of positive electrode materials

[0075] The multi-metal oxide obtained in step 1 is dispersed in a solution with a mass ratio of PC:EC:DMC:EMC:NMP=1:1:0.5:0.5:1 to prepare a solution with a mass fraction of 25%. The solution is continuously stirred and dispersed for 12 hours. The spray drying inlet temperature is set to 185°C and the outlet temperature is set to 105°C to obtain the positive electrode material of Example 1.

[0076] Example 2

[0077] 1. Preparation of multi-metal oxides

[0078] According to the chemical formula Na 0.95 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.95 F 0.05 The corresponding multi-metal oxides were synthesized by a high temperature solid phase method.

[0079] First, according to the stoichiometric ratio in the general chemical formula, NiO, CuO, MgO, Fe2O3, Co2O3, MnO2, TiO2, and NH4F raw materials are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1 hour. After rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10 hours, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground at 2800rpm in a sand mill for 1.5 hours. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then decreased to 450℃ at a rate of 3℃ / min and kept warm for 3 hours, and then cooled to room temperature with the furnace to obtain a multi-metal oxide.

[0080] 2. Preparation of positive electrode materials

[0081] The multi-metal oxide obtained in step 1 is dispersed in a solution with a mass ratio of PC:EC:DMC:EMC:NMP=1:1:0.5:0.5:1 to prepare a solution with a mass fraction of 25%. The solution is continuously stirred and dispersed for 12 hours. The spray drying inlet temperature is set to 185°C and the outlet temperature is set to 105°C to obtain the positive electrode material of Example 2.

[0082] Example 3

[0083] 1. Preparation of multi-metal oxides

[0084] According to the chemical formula Na 0.9 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.9 F 0.1 The corresponding multi-metal oxides were synthesized by a high temperature solid phase method.

[0085] First, according to the stoichiometric ratio in the general chemical formula, NiO, CuO, MgO, Fe2O3, Co2O3, MnO2, TiO2, and NH4F raw materials are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1 hour. After rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10 hours, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground at 2800rpm in a sand mill for 1.5 hours. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then decreased to 450℃ at a rate of 3℃ / min and kept warm for 3 hours, and then cooled to room temperature with the furnace to obtain a multi-metal oxide.

[0086] 2. Preparation of positive electrode materials

[0087] The multi-metal oxide obtained in step 1 is dispersed in a solution with a mass ratio of PC:EC:DMC:EMC:NMP=1:1:0.5:0.5:1 to prepare a solution with a mass fraction of 25%. The solution is continuously stirred and dispersed for 12 hours. The spray drying inlet temperature is set to 185°C and the outlet temperature is set to 105°C to obtain the positive electrode material of Example 3.

[0088] Example 4

[0089] 1. Preparation of multi-metal oxides

[0090] According to the chemical formula Na 0.95 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1.95 F 0.05The corresponding multi-metal oxides were synthesized by a high temperature solid phase method.

[0091] First, according to the stoichiometric ratio in the general chemical formula, NiO, CuO, MgO, Fe2O3, Co2O3, MnO2, TiO2, and NH4F raw materials are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1 hour. After rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10 hours, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground at 2800rpm in a sand mill for 1.5 hours. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then decreased to 450℃ at a rate of 3℃ / min and kept warm for 3 hours, and then cooled to room temperature with the furnace to obtain a multi-metal oxide.

[0092] 2. Preparation of positive electrode materials

[0093] The multi-metal oxide obtained in step 1 is dispersed in a solution with a mass ratio of PC: FEC: EC: DMC: EMC: NMP = 1: 0.5: 0.5: 0.5: 0.5: 1 to prepare a solution with a mass fraction of 25%. The solution is stirred and dispersed for 12 hours. The spray drying inlet temperature is set to 185°C and the outlet temperature is set to 105°C to obtain the positive electrode material of Example 4.

[0094] Example 5

[0095] 1. Preparation of multi-metal oxides

[0096] According to the chemical formula NaNi 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O2 was used to synthesize the corresponding multi-metal oxides by a high-temperature solid-phase method.

[0097] First, according to the stoichiometric ratio in the general chemical formula, the raw materials of NiO, CuO, MgO, Fe2O3, Co2O3, MnO2, and TiO2 are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1 hour. After rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10 hours, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground at 2800rpm in a sand mill for 1.5 hours. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10 hours, then decreased to 450℃ at a rate of 3℃ / min and kept warm for 3 hours, and then cooled to room temperature with the furnace to obtain a multi-metal oxide.

[0098] 2. Preparation of positive electrode materials

[0099] The multi-metal oxide obtained in step 1 is dispersed in a solution with a mass ratio of PC:EC:DMC:EMC:NMP =1:1:0.5:0.5:1 to prepare a solution with a mass fraction of 25%. The solution is continuously stirred and dispersed for 12 hours. The spray drying inlet temperature is set to 185°C and the outlet temperature is set to 105°C to obtain the positive electrode material of Example 5.

[0100] Comparative Example 1

[0101] According to the chemical formula NaNi 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O2 is synthesized into the corresponding multi-metal oxide by a high-temperature solid phase method, which is the positive electrode material of this comparative example.

[0102] First, according to the stoichiometric ratio in the general chemical formula, the raw materials of NiO, CuO, MgO, Fe2O3, Co2O3, MnO2, and TiO2 are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1h, and after rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10h, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground with a sand mill at 2800rpm for 1.5h. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10h, then reduced to 450℃ at a rate of 3℃ / min and kept warm for 3h, and then cooled to room temperature with the furnace to obtain the positive electrode material of Comparative Example 1.

[0103] Comparative Example 2

[0104] According to the chemical formula NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is synthesized into the corresponding multi-metal oxide by a high-temperature solid phase method, which is the positive electrode material of this comparative example.

[0105] First, according to the stoichiometric ratio in the chemical formula, NiO, Fe2O3, and MnO2 raw materials are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill is adjusted to 2500rpm for grinding for 1h, and after rotary evaporation, it is placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min for 10h, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate are added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the sand mill is ground at 2800rpm for 1.5h, and the spray drying air inlet temperature is set to 185℃, and the air outlet temperature is set to 105℃. The ground material is dried to obtain a spherical precursor powder material; the precursor is placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept for 10h, and then reduced to 450℃ at a rate of 3℃ / min and kept for 3h, and then cooled to room temperature with the furnace to obtain the positive electrode material of Comparative Example 2.

[0106] Comparative Example 3

[0107] According to the chemical formula NaNi 0.25 Cu 0.15 Fe 0.2 Ti 0.2 Mn 0.2 O2 is synthesized into the corresponding multi-metal oxide by a high-temperature solid phase method, which is the positive electrode material of this comparative example.

[0108] First, according to the stoichiometric ratio in the general chemical formula, the raw materials of NiO, Fe2O3, MnO2, CuO, and TiO2 are added to anhydrous ethanol to prepare a solution with a mass fraction of 20%. The sand mill was adjusted to 2500rpm for grinding for 1h, and after rotary evaporation, it was placed in a tube furnace and heated to 450℃ at a heating rate of 3℃ / min and kept warm for 10h, and then cooled to room temperature with the furnace; the sintered material and an excess of 5% sodium carbonate were added to anhydrous ethanol to prepare a solution with a mass fraction of 40%, and the solution was ground with a sand mill at 2800rpm for 1.5h. The spray drying inlet temperature was set to 185℃, and the outlet temperature was set to 105℃. The ground material was dried to obtain a spherical precursor powder material; the precursor was placed in a tube furnace, heated to 850℃ at a heating rate of 5℃ / min and kept warm for 10h, then reduced to 450℃ at a rate of 3℃ / min and kept warm for 3h, and then cooled to room temperature with the furnace to obtain the positive electrode material of Comparative Example 3.

[0109] Effect Example

[0110] The positive electrode materials of Examples 1-5 and Comparative Examples 1-3 were respectively used to prepare corresponding finished battery cells according to the following steps:

[0111] Each positive electrode material is mixed with the conductive agent Super P and the binder (PVDF, polyvinylidene fluoride) in a mass ratio of 95:3:2, and an appropriate amount of NMP is added as a solvent. Stir well and pass through a 200-mesh sieve after vacuum defoaming. The resulting slurry is coated on aluminum foil, dried at 110°C in vacuum for 12 hours, and cut into 45mm*58mm positive electrode sheets after 7Mpa rolling. Hard carbon is selected as the negative electrode, and hard carbon is mixed with the conductive agent Super P, CMC, and SBR in a mass ratio of 94:2:1.5:2.5. An appropriate amount of water is added as a solvent, stirred evenly, and passed through a 200-mesh sieve after vacuum defoaming. The resulting slurry is coated on the current collector of aluminum foil, dried at 95°C in vacuum for 12 hours, and cut into 47mm*60mm negative electrode sheets after 2Mpa rolling. The positive and negative electrodes that have been cut are re-baked to make the moisture content of the positive electrode less than 50ppm and the moisture content of the negative electrode less than 200ppm. Five positive electrodes and six negative electrodes are stacked, 2g of electrolyte is injected, and the battery is formed at a rate of 0.1C, aged at 45℃ for 48h, and the finished battery cells are obtained by volume separation.

[0112] The cell capacity and cycle performance of the obtained cells were tested using a discharge rate of 1C:

[0113] The results are shown in Table 1.

[0114] Table 1

[0115]

[0116] As shown in Table 1, the battery cell made of the positive electrode material obtained in the embodiment of the present invention (a seven-element metal oxide with an artificial CEI film formed on the surface) can still maintain a capacity retention rate of more than 89% after 600 cycles when the capacity is not less than 170 mAh; and when the positive electrode material is further doped with F, the capacity retention rate can be as high as more than 92%. In contrast, in Comparative Examples 1-3, when no artificial CEI film is formed and F is doped, the battery cells made of ternary or even pentaary metal oxides have a capacity retention rate of only 85.2% at most. This shows that when the positive electrode material of the present invention is actually used in a battery cell, its cycle capacity retention rate can be significantly improved.

[0117] Correspondingly, when it is further applied to sodium-ion batteries, it can also maintain excellent cycle performance.

Claims

1. A method for preparing a positive electrode material, characterized in that: The preparation method of the positive electrode material comprises the following steps: drying a mixed solution of a multi-metal oxide and an organic solvent to obtain the positive electrode material; wherein, The metals in the multi-metal oxide include a first metal and a second metal; the first metal is Na, and the second metal is selected from at least five of Ni, Cu, Mg, Fe, Co, Mn and Ti; The organic solvent includes a carbonate organic solvent.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: The carbonate organic solvent is selected from one or more of PC, EC, DMC, EMC and fluorinated compounds thereof; Preferably, the carbonate organic solvent is PC, EC, DMC and EMC; the mass ratio of PC, EC, DMC and EMC is preferably (0.5-1):(0.5-1):(0.5-1):(0.5-1), for example, 1:1:0.5:0.5; Preferably, the carbonate organic solvent is PC, FEC, EC, DMC and EMC; the mass ratio of PC, FEC, EC, DMC and EMC is preferably (0.5-1):(0.5-1):(0.5-1):(0.5-1):(0.5-1), for example, 1:0.5:0.5:0.5:0.

5.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The organic solvent further comprises an alkane organic solvent; the alkane organic solvent is preferably N-methylpyrrolidone; And / or, in the organic solvent, the mass ratio of the carbonate organic solvent to the alkanone organic solvent is 0.1:1-5:1, preferably 3:1; Preferably, the organic solvent is PC, EC, DMC, EMC and NMP; the mass ratio of PC, EC, DMC, EMC and NMP is preferably 1:1:0.5:0.5:1; Preferably, the organic solvent is PC, FEC, EC, DMC, EMC and NMP; the mass ratio of PC, FEC, EC, DMC, EMC and NMP is preferably 1:0.5:0.5:0.5:0.5:1; And / or, based on the mass of the mixed solution, the mass fraction of the multi-metal oxide is 20-30%, preferably 25%.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: In the multi-metal oxide, the second metal is Ni, Cu, Mg, Fe, Co, Mn and Ti; Preferably, the chemical formula of the multi-metal oxide is Na (0.9-1) Ni (0.1-0.25) Cu (0.1-0.2) Mg (0.05-0.15) Fe (0.05-0.15) Co (0.05-0.1) Mn (0.1-0.25) Ti (0.1-0.25) O (1.9-2) ; More preferably, the chemical formula of the multi-metal oxide is NaNi 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O2; And / or, the multinary metal oxide further comprises F; Preferably, the chemical formula of the multi-metal oxide is Na (0.9-1) Ni (0.1-0.25) Cu (0.1-0.2) Mg (0.05-0.15) Fe (0.05-0.15) Co (0.05-0.1) Mn (0.1-0.25) Ti (0.1-0.25) O (1.9-2) F (0-0.1) ; More preferably, the chemical formula of the multi-metal oxide is Na 0.98 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0. 2O 1.98 F 0.02 ; More preferably, the chemical formula of the multi-metal oxide is Na 0.95 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0. 2O 1.95 F 0.05 ; More preferably, the chemical formula of the multi-metal oxide is Na 0.9 Ni 0.15 Cu 0.15 Mg 0.1 Fe 0.1 Co 0.1 Mn 0.2 Ti 0.2 O 1. 9F 0.1 .

5. The method for preparing the positive electrode material according to claim 1, characterized in that: The drying method is spray drying or oven drying; preferably spray drying; The inlet air temperature of the spray drying is preferably 185°C, and the outlet air temperature is preferably 105°C. And / or, the preparation of the mixed solution comprises dispersing the multi-metal oxide in the organic solvent; Wherein, the dispersion is preferably agitated dispersion; the agitated dispersion time is preferably 12 hours; And / or, the preparation method of the multi-metal oxide is a high temperature solid phase method; preferably, the preparation method of the multi-metal oxide comprises the following steps: S1, a mixed solution A of a second metal precursor and a solvent A, grinding, and sintering once; S2, grinding, drying and secondary sintering of a mixed solution B of a product obtained by primary sintering, a first metal precursor and a solvent B.

6. The method for preparing the positive electrode material according to claim 5, characterized in that: In step S1, the second metal precursor is selected from at least five of a Ni precursor, a Cu precursor, a Mg precursor, a Fe precursor, a Co precursor, a Mn precursor and a Ti precursor, for example, selected from at least five of NiO, CuO, MgO, Fe2O3, Co2O3, MnO2 and TiO2; And / or, in step S1, the solvent A is anhydrous ethanol; And / or, in step S1, when the multi-metal oxide further includes F, the mixed solution A further includes fluoride, such as sodium fluoride and / or ammonium fluoride; And / or, in step S1, based on the total mass of the mixed solution A, the sum of the mass fractions of the second metal precursor and the fluoride is 20%; And / or, in step S1, the grinding is performed in a sand mill; And / or, in step S1, the grinding speed is 2500 rpm; And / or, in step S1, the grinding time is 1 hour; And / or, in step S1, the primary sintering is performed in a tube furnace; And / or, in step S1, the primary sintering temperature is 450° C.; And / or, in step S1, the time of the first sintering is 10 hours; Preferably, in step S1, the primary sintering is heated to 450°C at a heating rate of 3°C / min and then kept at this temperature for 10 hours; And / or, in step S1, a rotary evaporation step is further included between the grinding and the primary sintering.

7. The method for preparing the positive electrode material according to claim 5, characterized in that: In step S2, the first metal precursor is sodium carbonate; And / or, in step S2, the solvent B is anhydrous ethanol; And / or, in step S2, the grinding is performed in a sand mill; And / or, in step S2, the grinding speed is 2800 rpm; And / or, in step S2, the grinding time is 1.5h; And / or, in step S2, the drying method is spray drying or oven drying; preferably spray drying; The inlet air temperature of the spray drying is preferably 185°C, and the outlet air temperature is preferably 105°C. And / or, in step S2, the secondary sintering is performed in a tube furnace; And / or, in step S2, the secondary sintering comprises the following steps: heating to 850°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, then reducing the temperature to 450°C at a rate of 3°C / min, and keeping the temperature for 3 hours.

8. A positive electrode material, characterized in that The positive electrode material is prepared by the method for preparing the positive electrode material according to any one of claims 1 to 7.

9. A sodium ion battery, characterized in that: The positive electrode of the sodium ion battery comprises the positive electrode material as claimed in claim 8.

10. Use of the positive electrode material according to claim 8 or the sodium ion battery according to claim 9 in the field of electrochemistry.